Sebagai Instrumen Penguatan Karakter Tanggung Jawab Dan Disiplin Mahasiswa Hukum Keluarga Islam Semester 1 Di Universitas Islam Tribakti Lirboyo Kediri - Mamluaturrohmah; Ali Riyadi; Tasi’ Nugroho Mauloyo (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
This study aims to analyze the role of Civic and Pancasila Education (PPKn) as an instrument for strengthening the character of responsibility and discipline among first-semester students of the Islamic Family Law Study Program at Universitas Islam Tribakti Lirboyo Kediri. The background of this study stems from the importance of character education in higher education, particularly related to discipline and responsibility as fundamental values for shaping good citizens. This research employs a descriptive qualitative approach using observation, interviews, and documentation techniques. The findings indicate that PPKn plays a significant role in character development through learning plans that include character indicators, active and collaborative learning practices, lecturer role modeling, and evaluation systems that emphasize moral and ethical aspects of students. Supporting factors in character strengthening include the pesantren-based campus culture, lecturer exemplary behavior, and Islamic value–based learning approaches, while inhibiting factors include students’ low personal awareness and technological distractions. Overall, PPKn functions as an effective medium for fostering student discipline, responsibility, and awareness of national identity and ethical conduct.